Design values for experience - Zadel Velásquez, Vanessa Lucianna (2022)
This chapter addresses the formation of values through experiential learning and the incorporation of otherness in the subject Architectural Design IV, section 425, of the Architecture School of the University of Lima. The methodology and steps carried out within the practical teaching-learning process will be presented as a replicable good practice in order to raise awareness about the fundamental role that the user has in any architectural project. The course raises students’ awareness about the need to include a diversity of users (with and without disabilities), and about accessibility and the concept of universal design in the development of their design proposals. This methodology has been used since 2018. This chapter is part of the author's doctoral research. It developed under a qualitative research paradigm using multiple observation techniques. The selected populations are students of the Architecture School of the University of Lima and the sample corresponds to the students enrolled in section 425 of the course Architectural Design IV. Depending on the cycle, there can be 12 or 24 students.